Achievements And Challenges In Gynecology: An Analysis Of Modern Diagnostic And Treatment Approaches (Eurasian Medical Research Periodical, 2025)
The field of gynecology has undergone substantial transformations in recent years, with the introduction of advanced diagnostic tools and innovative treatment methodologies. This article explores the achievements in gynecology, focusing on breakthroughs in early detection, minimally invasive surgeries, and personalized treatment. Despite these advancements, challenges remain, particularly concerning accessibility, the integration of new technologies into clinical practice, and the rising concerns over the long-term effects of some treatments. The purpose of this article is to evaluate the current state of gynecology, addressing both the positive strides made and the ongoing obstacles that require attention